Numerical Solution of a TwoDimensional Dynamic Related Problem of Thermal Support - Yu.S. Yusupov (Genius Journals, 2022)
Related thermodynamic elastic boundary problems based on Ilyushin's theory of deformation have been formulated. Two types of explicit and implicit two-dimensional schemes have been constructed using the finite difference method. In the case of an explicit scheme, the numerical solution of the problem is based on a recurrence relation. In the case of an implicit scheme, the method of solving the problem is reduced to the use of the "run" method. Comparison of the numerical results obtained by the two methods shows that they are quite close
Keywords: Deformation; displacement; temperature; heat resistance